Cine foro como estrategia educativa para prevenir el consumo de alcohol en los estudiantes del noveno año paralelo c, de la unidad educativa fisco misional San Francisco de Asís, 2018-2019. - Sarango Leon, Viviana Nathaly (2019)
Alcohol consumption is one of the most common attitudes among adolescents, posing a risk in itself and for the associated problems it poses; therefore, the research deals with: Film forum as an educational strategy to prevent alcohol consumption in students of the ninth parallel year C, of the Educational Fiscommissional Unit San Francisco de Assisi, 2018-2019. The overall objective was: Implement the Educational Forum Film Strategy to prevent alcohol consumption. It was a quantitative study, descriptive, cross-sectional, and quasi-experimental design with a single group. The Scale of Intent and Attitudes towards Alcohol Consumption was applied in a sample of 41 students aged 12 to 14; methods were used: scientific, inductive, deductive, analytical, synthetic, and statistical (Karl Pearson linear correlation coefficient (r)). The results (pre-test) show that 63.41% of students had a positive (greater intention) attitude towards alcohol consumption; after the implementation of the alternative proposal (post-test) 85.37% have a negative attitude (less intention) towards alcohol consumption. The results of the validation of the strategy (R of Pearson) reached a value of r-0.55, means a mean positive correlation. It is concluded that those investigated presented attitudes of greater intension towards alcohol consumption, with the educational strategy of forum cinema implemented, changes in attitudes were achieved; validating the strategy in this way because after analyzing and clarifying what he saw, he managed to take it to a conscious plane, broadening his gaze on the reality of alcohol consumption that adolescents live.